The role of the tumor primary chemosensitivity relative to the success of the medical-surgical management in patients with advanced ovarian carcinomas. (November 2021) - You, Benoit; Freyer, Gilles; Gonzalez-Martin, Antonio; Lheureux, Stephanie; McNeish, Iain; Penson, Richard T.; Pignata, Sandro; Pujade-Lauraine, Eric
Highlights: In ovarian cancer patients, the 1st-line treatment relies on surgery and chemotherapy. The prognostic role of the chemotherapy efficacy has been insufficiently addressed. Indicators of the chemosensitivity include pathological, genomic or circulating markers. Both the surgery completeness and chemosensitivity impact the treatment success. The debulking surgery utility may differ according to the primary chemosensitivity. Abstract: In patients with advanced ovarian carcinomas, the first-line treatment has historically relied on debulking surgery and platinum-based chemotherapy. If the major therapeutic/prognostic role of the surgery part is well understood, and integrated in disease-management algorithms, the impact of chemotherapy efficacy has been insufficiently addressed. This review describes the main indicators of the chemosensitivity reported in the literature (pathological response score & biomarkers; genomic alterations; DNA scars; imaging; and circulating tumor markers), and investigates the respective roles of the debulking surgery and tumor primary chemosensitivity relative to the success of the comprehensive medical-surgical treatment. The tumor primary chemosensitivity exhibits a major independent prognostic impact on the feasibility of complete interval debulking surgery after neoadjuvant chemotherapy, risk of subsequent platinum-resistant relapse, efficacy of subsequent maintenance therapies with bevacizumab or PARP inhibitors, progression-free survival, overall and long-term survival. While both the completeness of the surgery and the tumor primary chemosensitivity are undoubtedly major prognostic factors, the impact of the surgery may differ according to the primary chemosensitivity. This assumption raises a potential new concept: in patients with advanced ovarian carcinomas, the maximum tumor debulking should ideally be both biological (induced by systemic treatments) and physical (induced by surgery) for maximizing patient survival. Besides BRCA and HRD biomarkers, future trials and algorithms may integrate indicator(s) of the tumor primary chemosensitivity for guiding more subtly the surgical and medical management in first-line setting. Moreover, such a parameter would help in the development of novel approaches meant to reverse the resistance to chemotherapy and PARP inhibitors.